Digital Transformation in Semiconductor Manufacturing: Proceedings of the 1st and 2nd European Advances in Digital Transformation Conference, EADTC 2018, Zittau, Germany and EADTC 2019, Milan, Italy - Keil, Sophia; Lasch, Rainer; Lindner, Fabian; Lohmer, Jacob (Lecture Notes in Electrical Engineering, 2020)
This open access book reports on cutting-edge electrical engineering and microelectronics solutions to foster and support digitalization in the semiconductor industry.Based on the outcomes of the European project iDev40, which were presented at the two first conference editions of the European Advances in Digital Transformation Conference (EADCT.